2008
DOI: 10.1016/j.brainres.2007.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Sodium intake by hyperosmotic rats treated with a GABAA receptor agonist into the lateral parabrachial nucleus

Abstract: Inhibitory mechanisms in the lateral parabrachial nucleus (LPBN) and central GABAergic mechanisms are involved in the regulation of water and NaCl intake. Besides increasing fluid depletion-induced sodium intake, the activation of GABA(A) receptors with muscimol into the LPBN also induces ingestion of 0.3 M NaCl in normonatremic, euhydrated rats. It has been suggested that inhibitory mechanisms activated by osmotic signals are blocked by GABA(A) receptor activation in the LPBN, thereby increasing hypertonic Na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…Similar to previous reports [16,20,31], the LPBN injection sites were centered in the central lateral and dorsolateral portions of the LPBN. Figure 1 shows the typical LPBN injection sites.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…Similar to previous reports [16,20,31], the LPBN injection sites were centered in the central lateral and dorsolateral portions of the LPBN. Figure 1 shows the typical LPBN injection sites.…”
Section: Resultssupporting
confidence: 87%
“…In a recent study [20], the authors also showed that the blockade of LPBN inhibitory mechanisms by injections of muscimol in this area also induced 0.3 M NaCl intake in fluid replete rats and in rats treated with intragastric 2 M NaCl load, suggesting that the increase in plasma osmolarity subsequent to NaCl ingestion does not appear to prevent further salt intake when GABA A receptors in the LPBN are activated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparably large water intakes after sc PEG, and enhanced intakes of 0.4 M NaCl after DOCA treatment, also have been observed in rats with capsaicin-induced destruction of peripheral sensory nerves (Curtis & Stricker, 1977). Furthermore, very large intakes of 0.3 M NaCl by rats have been observed after bilateral injection of various drugs into the lateral PBN in combination with systemic injection of hypertonic saline and other dipsogens (Kimura et al, 2008; Menani, De Luca, Thunhorst, & Johnson, 2000), as if the normal inhibition of salt appetite had been removed (see review by Stricker, 2004). Similarly, rats with ibotenic acid-induced lesions of the LPBN consumed relatively large amounts of water in one-bottle tests when they were injected with AngII but not with hypertonic saline (Edwards & Johnson, 1991; see also Ohman & Johnson, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…The activation of GABA A receptors by muscimol (a GABA A agonist) injected into the LPBN induces the ingestion of water and 0.3 M NaCl solution in both euhydrated and hyperosmotic cell-dehydrated rats, with the effect on sodium intake being reversed by the administration of bicuculline, a GABA A antagonist 34.…”
Section: Main Neural Pathways Involved In the Regulation Of Ecf Volummentioning
confidence: 99%